2011
DOI: 10.1039/c0ob00673d
|View full text |Cite
|
Sign up to set email alerts
|

Study of cavity size and nature of bridging units on recognition of nucleotides by cyclophanes

Abstract: We synthesized a few novel cyclophanes CP-1 to CP-4 containing anthracene units linked together through different bridging and spacer groups and have investigated their interactions with various nucleosides and nucleotides. Of these systems, CP-1 and CP-3 showed selectivity for 5'-GTP and 5'-ATP as compared to other nucleotides and nucleosides, whereas negligible selectivity was observed with CP-2 and CP-4. Interestingly, CP-1, CP-2 and CP-3 exhibited significant binding interactions with the fluorescent indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 76 publications
(9 reference statements)
1
14
0
Order By: Relevance
“…Previous research has demonstrated HPTS quenching by electron transfer with viologen moieties and in p-bond interactions with other aromatic compounds, including caffeine, theobromine, and theophylline. [25][26][27][28] Based on these electrontransfer binding interactions conrmed previously through uorescence and NMR titration and corroborated with cyclic voltammetry or mathematical modelling, we hypothesized that HPTS uorescence may be quenched through a similar binding complex with BPA, and that this may be distinguishable from quenching by similarly structured EDC and hormone comparators. To answer this, we investigated the BPA-HPTS binding interaction in contrast with the binding interactions of 17b-estradiol (E2), a natural estrogen, nonylphenol (NP), a structurally similar suspected endocrine disruptor, and nonspecic compounds in wastewater effluent (Fig.…”
Section: Introductionmentioning
confidence: 54%
“…Previous research has demonstrated HPTS quenching by electron transfer with viologen moieties and in p-bond interactions with other aromatic compounds, including caffeine, theobromine, and theophylline. [25][26][27][28] Based on these electrontransfer binding interactions conrmed previously through uorescence and NMR titration and corroborated with cyclic voltammetry or mathematical modelling, we hypothesized that HPTS uorescence may be quenched through a similar binding complex with BPA, and that this may be distinguishable from quenching by similarly structured EDC and hormone comparators. To answer this, we investigated the BPA-HPTS binding interaction in contrast with the binding interactions of 17b-estradiol (E2), a natural estrogen, nonylphenol (NP), a structurally similar suspected endocrine disruptor, and nonspecic compounds in wastewater effluent (Fig.…”
Section: Introductionmentioning
confidence: 54%
“…The combination of a water‐soluble ammonium‐pillar[6]arene with dapoxyl sodium sulfonate, as well as Zn II complexes with fluorescein, can selectively detect ATP in buffered solutions. In contrast, GTP prefers to displace HPTS (8‐hydroxypyrene‐1,3,6‐trisulfonic acid) from the positively charged cyclophanes and a porphyrin–pyridinium conjugate . A similar strategy was used by Schäferling and co‐workers, who used HPTS together with bipyridinium salt modified with triethylamine subunits .…”
Section: Indicator Displacement Assaymentioning
confidence: 99%
“…[20][21][22] This work hasi nspired other groups to evaluate interactions between cyclophanes andn ucleotides in aqueous solution. [23][24][25][26][27][28][29] These macrocycles have also been found to interact with G-quadruplex [30] and showa ntiproliferativea ctivity. [31] Interestingly,b is-naphthaline-derived macrocycles and bis-anthracene receptor 2 containing 2,2'-oxybis(ethylamine) as linker can recognize thymine-thymine mismatches in DNA ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s, Lehn proposed the use of cyclophanes as artificial receptors for nucleosides and nucleotides . This work has inspired other groups to evaluate interactions between cyclophanes and nucleotides in aqueous solution . These macrocycles have also been found to interact with G‐quadruplex and show antiproliferative activity .…”
Section: Introductionmentioning
confidence: 99%